Die Neuordnung der Logistikkette. Räumliche Auswirkungen unternehmensübergreifender Umstrukturierungsprozesse zwischen Industrie und Handel.: Das Beispiel Molkereiprodukte - Neiberger, Cordula (ERDKUNDE, 1997)
The world-wide economic crisis of recent years has led to massive economic restructuring processes, which are characterized by flexibilization at various levels (technologies, work hours etc) and by the optimization of processes across the boundaries once separating individual firms. Since the rationalization potential is particularly high in the field of logistics, it has been the one most affected by restructuring processes. This paper attempts to record the changes in the logistics field at the interface of food industry and food retail trade, and their spatial impacts. It became clear that the spatial structure of the distribution systems is dependant upon organizational changes within the industry, which are caused by new, flexible firm strategies for adapting to the markets. These processes are further strengthened by tendencies towards concentration in the affected fields of the food industry, trade and goods transport, and by changes in prevailing circumstances as, for example, EU legislation. Spatial changes have been observed at three different levels: first, the disintegration of regional system of supply and sales in the dairy industry and the subsequent increasing national linkage of producer and trade locations. Secondly, producer firms are clearly supporting policies to re-organize their distribution, by focussing above all on centralization of goods distribution. This in turn involves the dismantling of the different levels of the system and concentration on a single warehouse location in the immediate vicinity of the production (or one of the production sites). Small-scale distribution is handled through transshipment points. Thirdly, the centralization of storage systems is accompanied by the subcontracting of logistics services to those who offer them, the consequence of which is the taking over of goods into their systems. New location linkages create a higher volume of traffic, which can primarily be restrained by the utilization of existing bundling potentials. High potentials own service-provider systems, the locations of which do not coincide with the production locations, but are aligned to customer locations and transport favourability.